The safety and efficacy of immune checkpoint blockade in children, adolescents, and young adults: A systematic review and meta-analysis - Pedro C.A. Reis; João Evangelista Ponte Conrado; Mariana Macambira Noronha; Luís Felipe Leite da Silva; Erick Figueiredo Saldanha; Jonathan Metts (EJC Paediatric Oncology)
Background: Immune checkpoint blockade (ICB) has changed the treatment landscape for many types of adult cancer. However, for children, adolescents, and young adults (CAYAs) clinical experience lags behind that of adults. Therefore, we performed a systematic review and meta-analysis to evaluate the safety and efficacy of ICB in the CAYA population. Methods: We searched PubMed, Embase, and Cochrane Library databases for clinical trials evaluating ICB therapies for cancer in CAYA patients. We pooled the incidences of treatment-related adverse events (TRAEs), objective response rates (ORRs), stable disease (SD), and their corresponding confidence intervals (CIs). For the ORR and TRAE endpoints, we performed a subgroup analysis of each drug (PD-1, PD-L1, and CTLA-4) and tumor type. Results: 15 trials were included, comprising 797 patients (median age ranging from 6.5 to 16.0 years). All-grade TRAE rate of 66 % was found (95 % CI 60–71), while the proportion of grade 3/4 TRAEs was 19 % (95 % CI 14–27). For tumor type subgroup analysis of all-grade TRAEs and grade 3/4 TRAEs, solid tumors had the highest rates, 92 % (95 % CI 41–99) and 32 % (95 % CI 11–63), respectively. Fatigue, anemia, and nausea were the most frequently reported TRAEs. The ORR was 13 % (95 % CI 5–27). In subgroup analyses, PD-1 inhibitors and Hodgkin Lymphoma had the highest ORR, with 25 % (95 % CI 8–56) and 59 % (95 % CI 23–87), respectively. SD was noted in 21 % (95 % CI 14–30) of patients. Conclusions: Overall, ICB is well tolerated in CAYA patients with different cancer types, and certain subsets of CAYA cancer are ICB-responsive.